Asianising Singapore : the PAP's management of ethnicity - Vasil, Raj (Singapore : Heinemann Asia, 1995)
Issued under the auspices of Institute of Southeast Asian Studies
Keywords: Asians -- Singapore; Chinese -- Singapore; Ethnicity -- Singapore